SAT0181 ALTERATIONS OF PERIPHERAL LYMPHOCYTE SUBSETS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND THEIR CHANGES AFTER OUR NEW IMMUNOREGULATORY COMBINATION THERAPIES. (13th June 2020) - Zhang, J. Q.; Zhang, S. X.; Xue, L.; Qiao, J.; Qiu, M. T.; Zhao, R.; Chang, M. J.; Li, Y.; Luo, J.; Liu, G. Y.; Gao, C.; Li, X.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by abnormal activation of circulating lymphocytes and overproduction of autoantibodies 1 . Breakdown of self-tolerance is considered as a critical cause in the development of SLE 2 . However, the quantitative changes of lymphocyte subsets in SLE are unclear. Since low-dose IL-2 and several drugs have been used to promote the proliferation of regulatory T cells (Tregs) 3, we developed immunoregulatory therapies using these drugs to rebalance effector T cells with Tregs and test whether they are benefit to remission disease activity of SLE. Objectives: To observe the different levels of peripheral lymphocyte subsets at the first laboratory examination of SLE patients with those of healthy controls (HCs) and to evaluate the effect of immunoregulatory combination therapies on levels of lymphocyte subsets in patients with SLE. Methods: From September 2014 to December 2019, a total of 985 diagnosed patients with SLE (878 females, 107 males, mean age 42.99±13.37 years) and 206 healthy adults were enrolled in this retrospective cross-sectional study. And 795 patients with SLE (711 females and 84 males, mean age 38.26±15.242 years) were received the immunomodulatory drugs (IMiDs) such as low-dose interleukin-2, rapamycin, metformin, retinoic acid, coenzymes Q10 or other immunomodulatory treatments. The absolute numbers of T, B, NK, CD4 + T, CD8 + T, Th1, Th2, Th17 and CD4 + CD25 + Foxp3 + T regulatory cells (Tregs) in peripheral blood (PB) of these individuals were measured by Flow Cytometer (FCM) combined with standard absolute counting beads. Results: As compared with those of HCs, patients with SLE had lower absolute numbers of total T, NK, and CD4 + T but higher proportions of all lymphocyte subpopulations except NK, CD4+T cells( P < 0.001) (Figure 1 A, C). Notably, the absolute numbers and proportions of Tregs as well as Th1 in CD4 + T subsets were decreased ( P <0.05) (Figure 1 B, D). Further, there was a significant increase in the ratio of Teffs/Tregs such as Th1/Tregs, Th2/Tregs and Th17/Tregs ( P <0.05) (Figure 1 E). After receiving immunoregulatory combination therapies, the absolute numbers and proportions of T, NK, CD4 + T, and CD8 + T were increased, while the proportion of B cells was decreased (Figure 2 A, C); the absolute numbers of most CD4 + T subsets as well as the proportions of only Th1 and Tregs were significantly increased ( P < 0.001) (Figure 2 B, D). The ratios of Th1/Th2 and Th1/Tregs increased while that of Th17/Tregs and Th2/Tregs decreased ( P <0.01) (Figure 2 E). Conclusion: Quantitative and functional alterations of peripheral lymphocyte subsets, especially reduced Tregs, play crucial roles in the pathogenesis of the patients. Immunoregulatory combination therapies mainly promote the proliferation and functional recovery of Tregs to rebalance pro- and anti-inflammatory T cells in patients with SLE for patients' symptoms remission. References: [1]Sharabi A, Tsokos GC. T cell metabolism: new insights in systemic lupus erythematosus pathogenesis and therapy. Nat Rev Rheumatol 2020 doi: 10.1038/s41584-019-0356-x [published Online First: 2020/01/18] [2]Durcan L, O'Dwyer T, Petri M. Management strategies and future directions for systemic lupus erythematosus in adults. Lancet 2019;393(10188):2332-43. doi: 10.1016/S0140-6736(19)30237-5 [published Online First: 2019/06/11] [3]Spolski R, Li P, Leonard WJ. Biology and regulation of IL-2: from molecular mechanisms to human therapy. Nat Rev Immunol 2018;18(10):648-59. doi: 10.1038/s41577-018-0046-y [published Online First: 2018/08/10] Acknowledgments: None. Disclosure of Interests: None declared